VO.20 - Approval of unit rates of non-schedule item rebar welding works connected to plate of steel column - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the VO.20 - approval of unit rates of non-schedule item rebar welding works connected to plate of steel column of BRACU new campus project site.